2003
DOI: 10.1111/j.1745-4506.2003.tb00177.x
|View full text |Cite
|
Sign up to set email alerts
|

Case Studies of Local Food Purchasing by Central Iowa Restaurants and Institutions

Abstract: Through direct marketing of their products, many farmers are forming a stronger connection with their customers and obtaining premium prices for those products. Potential direct marketing customers for food producers are local restaurants and institutional foodservice operations. Benefits and challenges do exist for both foodservice operators and food producers interested in exploring this method of purchasing. A project tracking local food purchasing by nine Iowa restaurants and institutions is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 0 publications
1
51
0
7
Order By: Relevance
“…Other studies have found retail food services, most notably institutional sectors such as hospitals, are cautious about purchasing from local producers due to uncertainty about regulations ('Are we allowed to? '), taking extra time to search the market and communicate food specifications to the producer, and considering food safety (Gregoire & Strohbehn, 2002;Starr et al, 2003;Strohbehn & Gregoire, 2003). Most growers also identified benefits of selling to local restaurants, such as price premiums.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have found retail food services, most notably institutional sectors such as hospitals, are cautious about purchasing from local producers due to uncertainty about regulations ('Are we allowed to? '), taking extra time to search the market and communicate food specifications to the producer, and considering food safety (Gregoire & Strohbehn, 2002;Starr et al, 2003;Strohbehn & Gregoire, 2003). Most growers also identified benefits of selling to local restaurants, such as price premiums.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the author suggested that growth of LGP programs required reducing transaction costs, to which grower collaboration and improved vertical coordination between growers and produce distributors was the key. Strohbehn (2003) presented empirical evidence that food buyers for commercial and institutional food services in Iowa have strong interest in supporting local farmers, providing fresher and high quality foods, and lowering associated transportation costs. Data from the study also showed that operations wish to know the sources of foods purchased.…”
Section: Business To Business Research In Local Foodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Özet olarak restoranların yerel ürün kullanmasının avantajlarını sıralamak gerekirse sırasıyla; azalan lojistik mesafesi ile azalan enerji tüketimi, yerel kalkınmanın desteklenmesi, daha taze ürünlerin tüketimi, tedarikçi ve hizmet sa layıcı arasında ileti im ve iyi ili kiler, gıdanın az miktarda ve daha kaliteli olması, yerel ürün kullanan i letmelerin daha fazla tercih edilmesinden bahsedilebilir (Murphy ve Smith, 2009;Ortiz, 2010;Schwartz, 2011;Sharma, Moon, ve Strohbehn, 2014;Strohbehn ve Gregoire, 2003). Yerel ürün satın alınmasındaki zorlukları ise; yılın her dönemi olmayı ı, birden fazla tüketiciyle çalı ılma zorunlulu u, yeterince miktarın olmama ihtimali, tutarsız paket boyutları, yerel ve bölgesel düzenlemeler, güvenilir gıda miktarı, sipari prosedürleri, gıda güvenli i konuları, zamanında teslimat, yemek hazırlanmasındaki i gücü, üretim maliyetleri, ödeme ko ulları olarak sıralamak mümkündür (FPC, 2003;Ortiz, 2010;Schwartz, 2011;Sharma ve di ., 2009;Strohbehn ve Gregoire, 2003).…”
Section: Yöresel Restoranlarda Yerel üRün Satın Almaunclassified
“…Yerel ürün satın alınmasındaki zorlukları ise; yılın her dönemi olmayı ı, birden fazla tüketiciyle çalı ılma zorunlulu u, yeterince miktarın olmama ihtimali, tutarsız paket boyutları, yerel ve bölgesel düzenlemeler, güvenilir gıda miktarı, sipari prosedürleri, gıda güvenli i konuları, zamanında teslimat, yemek hazırlanmasındaki i gücü, üretim maliyetleri, ödeme ko ulları olarak sıralamak mümkündür (FPC, 2003;Ortiz, 2010;Schwartz, 2011;Sharma ve di ., 2009;Strohbehn ve Gregoire, 2003).…”
Section: Yöresel Restoranlarda Yerel üRün Satın Almaunclassified